2014
DOI: 10.1177/0022034514524782
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically Induced Corrosive Properties of the Titanium Surface

Abstract: Corrosion of titanium is the major concern when it is used for dental treatment. This study aimed to investigate the mechanism of the microbiologically induced corrosive properties of titanium. An experimental well was made of polymethyl methacrylate with pure titanium at the bottom. Viable or killed cells of Streptococcus mutans were packed into the well, and pH at the bacteria-titanium interface was monitored with and without glucose. Before and after 90-minute incubation, the electrochemical behavior on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 22 publications
5
41
0
Order By: Relevance
“…In addition, the oral microbiome has the potential to disrupt the biocompatible titanium dioxide surface layer . A specific example is Streptococcus mutans , which has been shown to increase the corrosion current and to induce titanium corrosion . We have shown that oral bacterial taxa are capable of affecting titanium electro‐conductive properties and can lead to spontaneous generation of electrical potential and accelerated titanium dissolution from titanium implants .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the oral microbiome has the potential to disrupt the biocompatible titanium dioxide surface layer . A specific example is Streptococcus mutans , which has been shown to increase the corrosion current and to induce titanium corrosion . We have shown that oral bacterial taxa are capable of affecting titanium electro‐conductive properties and can lead to spontaneous generation of electrical potential and accelerated titanium dissolution from titanium implants .…”
Section: Discussionmentioning
confidence: 95%
“…Streptococcus mutans, which has been shown to increase the corrosion current 49 and to induce titanium corrosion. 50 We have shown that oral bacterial taxa are capable of affecting titanium electro-conductive properties and can lead to spontaneous generation of electrical Shannon Diversity Streptococcus Relative Abundance iv.…”
Section: Interpretation Of the Study Supported By Existing Evidencementioning
confidence: 99%
“…Therefore, citric acid may act similarly, degrading the natural oxide film and interacting with the surface to form a TiH 2 layer that, posteriorly, is covered by a new spontaneously formed TiO 2 film. Additionally, because the oral biofilms can affect the electrochemical behavior of cpTi surface, discs only exposed to the treatments (without previous biofilm formation) were used in the electrochemical tests to check the direct influence of citric acid on titanium surface.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus species, especially S. mutans , are opportunistic bacteria known to accelerate corrosion of Ti‐based dental implants . Bacterial adhesion is expected to induce corrosion of metallic substrates via metabolic byproducts including lactic acid and hydrogen peroxide which can lower the corrosion resistance of Ti .…”
Section: Discussionmentioning
confidence: 99%